Aktuelle Aspekte in der Diagnostik und Therapie der obstruktiven Schlafapnoe - Stuck, Boris; Maurer, Joachim T. (HNO, 2016)
Over the past years, the diagnostic tools and therapeutic approaches for obstructive sleep apnea (OSA) have further evolved. Based on a review of current literature and the personal experiences of the authors, the most relevant developments are summarized in this article and discussed with regard to their impact on the clinical management of this disease. In the third edition of the “International Classification of Sleep Disorders”, the classification of sleep-disordered breathing was modified. Notably, additional clinical criteria for the diagnosis of OSA were established and out-of-center sleep testing was introduced as an alternative to polysomnography. Recent technical advancement of new diagnostic tools (e. g., peripheral arterial tonometry and pulse wave analysis) has further expanded the diagnostic possibilities. Drug-induced sleep endoscopy enables reliable assessment of the level and degree of upper airway obstruction. Whether this gain in diagnostic information leads to an improvement in surgical outcome is, however, still under discussion. The relevance of positional OSA has received increasing attention—the proportion of patients in whom sleeping position significantly impacts disease is reported to be above 50 %. For these patients, the introduction of the sleep position trainer has made a new therapeutic option available. Furthermore, hypoglossal nerve stimulation (upper airway stimulation) has substantially expanded the surgical spectrum of OSA treatment. For the established surgical treatment options, randomized trials with superior methodology have been published, particularly for bimaxillary advancement and tonsillectomy with uvulopalatopharyngoplasty. These developments are of particular interest for the otolaryngologist and will influence daily practice.
Gesehen am 20.08.2020
Online publiziert: 14. Dezember 2015